2018
DOI: 10.1097/pgp.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

Disease Distribution in Low-stage Tubo-ovarian High-grade Serous Carcinoma (HGSC): Implications for Assigning Primary Site and FIGO Stage

Abstract: The latest FIGO and TNM (eighth edition) staging systems for ovarian, tubal, and peritoneal neoplasms require primary site assignment as tubal/ovarian/peritoneal, but provide no guidance or criteria. Fewer than 10% of extrauterine high-grade serous carcinoma (HGSC) cases present at low stage (stage I/II). Low-stage cases offer a unique opportunity to understand the pattern of disease early in its evolution prior to wide dissemination and provide valuable evidence for guiding specimen handling and tumor staging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…25,26 It has also been shown that application of the SEE-FIM protocol increases the detection of premalignant and malignant tubal lesions. 27 Occult invasive cancer and serous tubal intraepithelial carcinoma lesion are identified in 0.9-8.5% of patients undergoing riskreducing salpingo-oophorectomy. 28 It is therefore possible that there has been increased detection of premalignant and malignant tubal lesions when combined with increased application of the SEE-FIM protocol and the state-of-science updated pathology protocols.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 It has also been shown that application of the SEE-FIM protocol increases the detection of premalignant and malignant tubal lesions. 27 Occult invasive cancer and serous tubal intraepithelial carcinoma lesion are identified in 0.9-8.5% of patients undergoing riskreducing salpingo-oophorectomy. 28 It is therefore possible that there has been increased detection of premalignant and malignant tubal lesions when combined with increased application of the SEE-FIM protocol and the state-of-science updated pathology protocols.…”
Section: Discussionmentioning
confidence: 99%
“…They are frequently confused with ovarian cancers in case of locally advanced disease and are clearly underestimated. They are unilateral in 85 % of cases [2] , with an average of 20 to 30 new cases reported each year [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an oncogenetic opinion is most often sought. Tubal cancer is also associated with overexpression of p53, HER-2/neu and c-myc [2] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations